ALTERNATIF PEMODELAN NUMERIK KOPEL THERMO-HYDRO -MECHANIC INJEKSI CO2 PADA FORMASI GEOLOGI BAWAH PERMUKAAN - Cahli Suhendi; Mohammad Rachmat Sule (Engineering Faculty Universitas Lampung, 2020)
CO2 injection into subsurface formations is a potential method to reduce CO2 gas emissions in the atmosphere. Geological and geophysical studies are carried out as an effort to analyze the storage capacity and potential risks. The results are then used to analyze the response of reservoir rock to the injected CO2 fluid. The effect of fluid injection on reservoir rocks is complex and involves a coupled system of fluid flow-geomechanics. CO2 fluid injection can increase fluid pressure that affects the local stress conditions of reservoir and surrounding rock. Meanwhile, changes in temperature due to the presence of CO2 fluid also affect reservoir rock stress, although not significantly. The complexity of the subsurface reservoir system includes thermomechanical and hydromechanical analysis involving multi-phase and multi-component fluids. To study these complex interactions, a program which can simulate the coupling between multi-phase and multi-component fluid-flows-geomechanics is needed. To accommodate these needs, Rutqvist et al (2002) have proposed a numerical modeling approach by linking TOUGH2-ECO2N and FLAC3D. In this study we developed an external program that linking TOUGH2 with different fluid modul (ECO2M), and FLAC3D using these approaches to run the coupled THM simulation automatically and seamlessly until the end of simulation.